Konsep Perancangan Fasilitas Pusat Pelatihan Bola Basket Kursi Roda di Kota Denpasar - I Putu Aldi Mustika Dinata; I Wayan Wirya Sastrawan; Ni Putu Ratih Pradnyaswari Anasta Putri (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
People with disabilities are currently free to do activities or have careers in several fields, including sports. Physical limitations are no longer an obstacle to becoming a professional athlete. Wheelchair basketball is one of the sports for athletes with disabilities that has continually developed and increased interest in the last few years. Including in Bali Province itself, wheelchair basketball often holds training camps in Denpasar City. However, until now there is only one wheelchair basketball training facility at the Bali Island School and its eligibility does not meet the proper standard. So that the idea of ​​a training center facility design for wheelchair basketball emerged. Not only as a sports facility, but also equipped with educational, commercial, recreational and athlete health facilities in accordance with the needs of a sports training center. This facility is a training center facility specifically for athletes with disabilities, so it must adjust to international standards for more ergonomic accessibility, especially for users with disabilities.